AN EXPLORATION OF POLICE OFFICER'S PERCEPTIONS OF THE CONTACT THEY HAVE WITH INDIVIDUALS EXPERIENCING MENTAL HEALTH PROBLEMS IN THE COMMUNITY. - Adshead, Vicki (2008)
This qualitative study is based on a group of nine police officers located in the East Midlands area. The study examines the police officers perceptions of the contact they have with individuals experiencing mental health problems in the community. It is understood that within the current era of community care the police have an increased amount of contact and responsibility in regards individuals with mental health problems. However there is little research aimed at discovering what this contact entails in the United Kingdom (UK). Therefore, nine semi-structured interviews were undertaken and audio-taped with the police officers. The data was analysed using an Interpretative Phenomenological Approach (IPA) and 4 key themes were identified. The themes highlighted that the police officers did not express a clear consensus over whether they thought there was a link between mental health problems and criminal behaviour. Furthermore they often felt confused and uncertain over their roles with individuals experiencing mental health problems. This further demonstrated a need for the police and mental health services to work in a collaborative way to ensure that individuals with mental health problems receive adequate care and support.